(untitled) (Conference Zone, 2022)
Pedagogy of primary education - upbringing, education of primary school students, the study of their specific psychological and physiological characteristics, as well as their intellectual, spiritual, moral and physical development studies issues.In a technological and digital-based learning environment, pedagogical innovation is a matter of integrating many levels of analysis, from individual to societal, and traditional to most innovative teaching and learning approaches